New insights into the antioxidant activity and cytotoxicity of arzanol and effect of methylation on its biological properties. (June 2017) - Rosa, Antonella; Atzeri, Angela; Nieddu, Mariella; Appendino, Giovanni
Graphical abstract: Highlights: The effect of the pyrone moiety methylation on the antioxidant activity and cytotoxicity of the natural phenol arzanol was investigated. Methylation was detrimental for antioxidant activity in lipid oxidation assays, providing evidence of structure-activity relationships. Arzanol inhibited lipid peroxidation in the Fe-NTA model of in vivo oxidative stress. Arzanol could selectively reduce viability in cancer cell lines (HeLa, B16F10, and Caco-2 cells). Abstract: The heterodimeric phloroglucinyl pyrone arzanol (Arz) has raised considerable interest because of its antiviral, anti-inflammatory, and antioxidant activity. We have investigated the effect of methylation of the pyrone moiety on the antioxidant activity and cytotoxicity of Arz. This manoeuvre, that left the polyphenolic moiety unscathed, was nevertheless detrimental for antioxidant activity in both the cholesterol thermal degradation- and the Cu 2+ -induced liposome oxidation assays, providing evidence of structure-activity relationships that go beyond the preservation of the polyphenolic pharmacophore. The antioxidant activity of Arz was retained also in the Fe-NTA model of in vivo oxidative stress, with protective effect on the oxidative degradation of plasmatic lipids, unsaturated fatty acids and cholesterol. Both Arz and methylarzanol (Me-Arz) were devoid of toxic effect on colonic differentiated Caco-2 cells up to 100 μM, but significantly reduced cancer Caco-2 cell viability at lower dosages. Arz could also selectively reduce viability of other cancer cell lines, [murine melanoma cells (B16F10 cells), human cervical carcinoma cells (HeLa cells)], suggesting that it can act as a selective modulator of cell processes typical of cancer cells. Taken together, our results qualify Arz as a lead structure for further in vivo investigation of its pharmacological potential.